การปกครองคณะสงฆ์ในยุคดิจิทัล: โอกาสและความท้าทาย - (ฉัตรชัย มูลสาร), พระศรีวชิรวาที (วารสาร มมร ยศสุนทรปริทรรศน์, 2024)
The governance of the Sangha in the digital age faces both opportunities and challenges that impact its operations and role within Thai society. Digital technologies such as the internet, social media, and various applications have provided the Sangha with the opportunity to disseminate Buddhist teachings to a broader audience in a more accessible format. Through the use of online platforms, monks are able to communicate with laypeople and respond to their spiritual needs more rapidly and efficiently. However, digital technologies also present challenges in terms of management, maintaining order within the Sangha, and protecting personal data. The use of technology in disseminating Buddhism must therefore consider ethics and adherence to the principles of Buddhist teachings to avoid potential negative consequences from improper use of technology. This article aims to reflect on both the opportunities and challenges in governing the Sangha in the digital era, as well as propose ways in which the Sangha can adapt to effectively utilize technology in governance and the dissemination of teachings in a manner that aligns with the principles of Buddhism.